The potential link between inflammatory bowel disease and male erectile dysfunction: mechanistic insights and novel therapeutic perspectives - Li, Shuxin; Cao, Hongliang; Liang, Yuwei; Lv, Chengsen; Ma, Yutao; Yang, Tong; Yuan, Bo; Wei, Wei (Frontiers in Immunology, 2026)
This review provides a comprehensive synthesis of the link between inflammatory bowel disease (IBD) and male erectile dysfunction (ED), with a distinct emphasis on underlying mechanisms and novel perspectives. We critically evaluate the evidence and then systematically elucidate the “gut-penis axis” detailing how gut-derived signals orchestrate a systemic inflammatory response that culminates in penile vascular dysfunction. A novel aspect of our work is the integration of psychological factors into a cohesive psychoneuroimmunological framework, linking stress, the cholinergic anti-inflammatory pathway, and direct pro-inflammatory neural circuits to ED pathogenesis. Beyond mechanistic insight, we examine the clinical implications of this connection, discussing the potential of anti-inflammatory therapies and the necessity of integrated management strategies that address both intestinal and sexual health. Our work aims to bridge knowledge gaps and stimulate targeted interventions to improve the quality of life for men living with IBD.